Answer:
![(B)r=(85)/(12)](https://img.qammunity.org/2021/formulas/mathematics/college/x137yth6ykk9vnnd54pbflv97simxbyft8.png)
Explanation:
Given a circle centre J
Let the radius of the circle =r
LK is tangent to circle J at point K
From the diagram attached
Theorem: The angle between a tangent and a radius is 90 degrees.
By the theorem above, Triangle JLK forms a right triangle with LJ as the hypotenuse.
Using Pythagoras Theorem:
![(6+r)^2=r^2+11^2\\(6+r)(6+r)=r^2+121\\36+6r+6r+r^2=r^2+121\\12r=121-36\\12r=85\\r=(85)/(12)](https://img.qammunity.org/2021/formulas/mathematics/college/dkhavjcyfhdlh1637w7lk66kf8q185s0l7.png)
The length of the radius,
![r=(85)/(12)](https://img.qammunity.org/2021/formulas/mathematics/college/zng91bbrlkd2489m828m6bb8to6vi3c9to.png)